The Tradition of Nyadokaken Pengantin in Osing Tribe Marriages in Indonesia: An 'Urf Perspective - Ansori, Moh. Khoirur Rizqi; Dahlan, Moh; Ishaq, Ishaq (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
This study examines the Nyadokaken pengantin tradition in the marriage of the Osing tribe in Kemiren Village, Banyuwangi, emphasizing its origins, execution, and legal standing under Islamic law. This research utilizes a qualitative methodology, encompassing participant observation, in-depth interviews, and recording while adopting a normative framework that integrates Pierre Bourdieu’s habitus theory as an analytical instrument. Research suggests that Nyadokaken began as a method for conflict settlement aimed at preserving familial unity. It possesses considerable societal significance, as families that renounce it encounter stigma and less social acknowledgment. From a fiqh standpoint, the tradition is classified as ‘urf shahih, as it conforms to Al-‘Adah Muhakkamah, meeting the standards of recognized customary practice in Islamic jurisprudence. This study enhances Islamic family law by examining how ‘urf shahih might incorporate local traditions into modern Islamic legal frameworks. Utilizing a sociocultural approach reconciles normative Islamic law with actual practices, providing insights into the adaptive characteristics of Islamic legal principles in Indonesia,